1979
DOI: 10.5006/0010-9312-35.10.461
|View full text |Cite
|
Sign up to set email alerts
|

Hydride Phases in Austenitic Stainless Steels

Abstract: Electrolytic charging of austenitic stainless steels with hydrogen induces formation of two distinct alloy hydride phases, both being unstable under normal atmospheric conditions. One of the new phases denoted Hγ, has the same Bravais lattice as austenite (fcc), whereas another, denoted Hε, exhibits an hcp structure. Compared with hydrogen-free austenite and ε-martensite, respectively, the lattice constants of hydride phases are larger by about 5%. During charging of austenitic stainless steels with hydrogen e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
2

Year Published

1986
1986
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(26 citation statements)
references
References 0 publications
4
20
2
Order By: Relevance
“…Takai et al [207] showed that the hydrogen adsorption capacity in ferrite is increased due to the hydrogen-enhanced production of strain-induced vacancies and dislocations. However, during annealing at 200 C, these defects were almost entirely annihilated, indicating that these were primarily vacancies. Models Figure 9 Schematic of macro-and micromechanism [147].…”
Section: Mesoscopic and Continuum Modelsmentioning
confidence: 99%
“…Takai et al [207] showed that the hydrogen adsorption capacity in ferrite is increased due to the hydrogen-enhanced production of strain-induced vacancies and dislocations. However, during annealing at 200 C, these defects were almost entirely annihilated, indicating that these were primarily vacancies. Models Figure 9 Schematic of macro-and micromechanism [147].…”
Section: Mesoscopic and Continuum Modelsmentioning
confidence: 99%
“…In numerous studies, the formation of hcp -martensite in 304-and 310-type austenitic stainless steels was observed as a result of hydrogen charging [3][4][5][6][7][8]. It was also reported that bcc ␣-martensite is formed during the outgassing of hydrogen from 304 stainless steel, whereas no ␣-martensite was detected in 310 stainless steel [7].…”
Section: Introductionmentioning
confidence: 97%
“…X-ray diffraction studies on cathodically hydrogen-charged austenitic stainless steels have been performed to investigate possible phase transformations due to hydrogen loading [1][2][3][4][5][6][7][8][9][10]. The austenitic stainless steels of AISI type 304 (composition close to Fe/Cr18/Ni10) and AISI type 310 (composition close to Fe/Cr25/Ni20) have been studied most extensively in this context.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last fifty years, materials scientists have spent many efforts to find a unique mechanism of HE. As a result of these efforts, three main competing models of HE were proposed: decohesion (e.g., [2]), hydride formation (e.g., [3]) and hydrogen-enhanced local plasticity (HELP) [4].…”
Section: Introductionmentioning
confidence: 99%